39.4k views
5 votes
Solve 7x-3+3x=4(4x-1)-5

User Sflee
by
5.3k points

2 Answers

4 votes

Answer:

6=6x (x=1)

Explanation:

7x-3+3x=4 (4x-1)-5

7x-3+3x=16x-4-2

So I have just multiplied out the brackets on the right side 4×4x and 4×1.

7x+3x=16x-4-2

Here I have just added the -3 from the left onto the right changing it to a positive and onto the -5 therefore getting -2.

10x=16x-3

Now I just added the numbers together on each side like 7x+3x and -4-2.

10x+6=16x

This is just moving the -6 onto the left side so we get a positive 6.

6=6x

I have simply done 16-10.

User RSK
by
5.1k points
6 votes

Answer:

x=1

Explanation:

User Osdf
by
6.6k points